The use of ECG gated myocardial perfusion spect in the evaluation of septal wall perfusion defect in patients with LBBB - Sayed, Mustafa; Shukkur, A; Biswas, G; Salman, H; Almohanadi, S (Heart views, 2008)
Introduction: Left bundle branch block (LBBB), affects septal wall thickening during systole, due to abnormal polarization pattern. However, in patients with LBBB, frequent septal perfusion defects are reported in Myocardial Perfusion SPECT even when there is no coronary stenosis on angiography. GATED Myocardial Perfusion SPECT (Single Photon Emission Tomography) is an accurate indicator and has shown high sensitivity and specificity to diagnose CAD. Septal perfusion defects in patients with LBBB is intensified during stress perfusion scintigraphy due to abnormal systolic phase in the septum, and abnormal conduction which gives a false appearance of reduced perfusion during the systolic phase. Patients and Method: Stress-rest Gated Myocardial Perfusion SPECT using Tc99m myoview was performed in 20 subjects with LBBB with probability of CAD. Visual analyses of the slice images and revision results of Gated SPECT study were done on end diastolic (ED), end systolic (ES) images, regional wall motion and wall thickness for evaluation of the perfusion of septum. Results: Visual analysis of stress-rest slices: 1) Reversible septal hypoperfusion was noted in 13 (65%) patients. 2) Fixed septal defects in 4 (20%). 3) Three patients (15%) had normal septal perfusion. Quantitative analysis of gated study: 1) Out of the 13 patients with reversible hypoperfusion, 8 (40%) show normal findings on Gated SPECT and only the remaining 5 (25 %) patients had true reversible hypoperfusion. 2) The 4 patients with fixed septal defects show normal findings on Gated SPECT Conclusion: The use of Gated myocardial perfusion scintigraphy particularly end-diastolic images can help in the evaluation of septal perfusion, wall motion and thickening and hence differentiate true perfusion defects from false patterns in cases of LBBB.